“Caracterización de la carga de combustible forestal muerto de las plantaciones forestales de Pinus patula Schiede ex Schltdl. & Cham. y Eucalyptus saligna Sm en el Parque Universitario Francisco Vivar Castro” - Granda Armijos, Anderson Leandro (2024)
Forest plantations are essential for life, playing a crucial role in sustainable development by producing wood, which is vital for balancing the supply and demand of timber products. In addition to their economic contribution, these plantations are crucial for environmental sustainability by regulating temperature and humidity. Their importance extends beyond wood production, encompassing economic, environmental, and conservation aspects. However, forest plantations are directly affected by forest fires due to their abundance of dead forest fuel, lack of silvicultural management, and exposure to environmental and geographical conditions that facilitate fire occurrence. The research was conducted in the Francisco Vivar Castro University Park with the aim of contributing to the understanding of fire behavior through the determination of the load of dead forest fuels present in the forest plantations of Pinus patula Schiede ex Schltdl. & Cham. and Eucalyptus saligna Sm. in the Francisco Vivar Castro University Park. A total of 15 temporary transects of 5 m x 20 m were installed per plantation, where planar intersections were nested for fuel load in the categories of light, moderate, and heavy (firm and rotten). For the litter-derived fuel, 30 quadrants of 50 cm x 50 cm were installed in each plantation. The relationship of environmental factors such as relative humidity, absolute humidity, temperature, wind speed, litter depth, and slope with the amount of dead forest fuel was analyzed. The total load of dead forest fuel in the pine plantation was 37.81 Mg ha-1, while for the eucalyptus plantation, it was 19.35 Mg ha-1, with the moderate/regular category having the highest load for both plantations. The Spearman correlation analysis for the pine plantation indicates that the maximum wind speed showed a moderate to strong positive association (r = 0.69) with a p-value of 0.003, while for the eucalyptus plantation, relative humidity recorded a strong negative association (r = -0.56) with a p-value of 0.0025. Likewise, the environmental factors that correlate most significantly with the load of dead forest fuel in both plantations are relative humidity, moisture content, wind speed, and temperature. Based on these results, Pinus patula Schiede ex Schltdl. & Cham. and Eucalyptus saligna Sm. plantations pose an imminent risk for the initiation of a forest fire